PRINCIPLES OF COMPLEX SYSTEMS OF PROTECTION PUBLIC INFORMATION RESOURCES - Юдін, О. К.; Бучик, С. С. (Science-based technologies, 2015)
The concept of the complex system of protection of state informative resources is entered in the articles. On the basis of principles of informative safety, general principles of construction of the systems of protection of information and taking into account basic principles the constructions of automatics system, generalized and the formed basic principles of construction of the complex system of protection of state informative resources. Offer is generalized flow diagram of protection of state informative resources.